A Spirit of Cosmopolitanism Happily Prevailing in Art: The Chinese Camera Club of South Africa and Transnational Networks of Photography. Issue 1 (2nd January 2018) - Corrigall, Malcolm
Abstract: The Chinese Camera Club of South Africa was formed in 1952 by members of Johannesburg's small Chinese community who found themselves excluded from local circuits of photography on the grounds of race. The membership of the Chinese Camera Club sought international recognition as well as local visibility by engaging with transnational networks of photography. In so doing, they became agents in the global dissemination of photographic practices and technologies and asserted a cultural cosmopolitanism that subverted the parochialism of apartheid's racial hierarchy. Alongside their cosmopolitan patterns of association, they also convened and sustained racially exclusive communities of photographic practice. They staged two international photographic salons in Johannesburg in 1956 and 1964 that were open to photographers from across the worldwide Chinese diaspora and thereby helped forge an imagined community of overseas Chinese photographers. In so doing, the Club and its members established a proprietorial connection with so-called "Chinese" approaches to photography and stressed their enduring connection to idealised and ahistorical notions of Chinese culture and civilisation. This paper explores both of these globally articulated identities—the cosmopolitan and the diasporic—as the result of transnational strategies that fostered autonomy and pride in the face of local racial discrimination.